Use of gamified augmented reality app in creating interest in learning english among vocational college students - Wang, Dan (2022)
With the advent of the Fourth Industrial Revolution, forms of gamification are constantly changing. Overlaying virtual elements such as Augmented Reality (AR) brings a whole new digital learning experience for students. The use of gamification and AR technology has proven effective in enhancing interest, an element that has long been considered crucial for students' learning and personal development. The focus of this qualitative case study is on the use of a gamified augmented reality app named XploreRAFE+ in the formation of interest in English learning among vocational college students in China. The research questions that drive this study are: 1. What is the process of interest formation and its relevant influencing factors among vocational college students in a gamified AR environment? 2. How does a gamified AR environment trigger students’ interest in English language learning? 3. How does a gamified AR environment immerse students in English language learning? 4. How does a gamified AR environment extend students’ learning experience? To answer these questions, data were collected from thirty-eight vocational college students via observation, interviews and document analysis over the course of one month. This study found that a gamified AR environment constructed through the use of the XploreRAFE+ app could create a meaningful learning environment. In such an environment, the process of the interest formation is a dynamic loop that includes piquing curiosity, experiencing optimal learning experience, and perceiving meaningfulness. Furthermore, its use raised students’ interest to learn English by fostering autonomy, competence, and relatedness with real life experience, all of which resonate with the main psychological need for intrinsic motivation. The use of the gamified AR app could also boost students’ confidence and improve their English learning experience. These findings have significant implications for theory and practice. The findings of the study are beneficial to teachers, vocational colleges, the Ministry of Education, researchers, instructional designers, and theory development.